Framing and Cultivating the Story of Crime: The Effects of Media Use, Victimization, and Social Networks on Attitudes About Crime. (June 2018) - Kort-Butler, Lisa A.; Habecker, Patrick
The current study extended prior research by considering the effects of media, victimization, and network experiences on attitudes about crime and justice, drawing on the problem frame, cultivation, real-word, and interpersonal diffusion theses. Data were from a survey of Nebraska adults ( n = 550) who were asked about their social networks; beliefs about media reliability; use of newspaper and news on TV, radio, and the Internet; and exposure to violence on TV, movies, and the Internet. Results indicated that viewing TV violence predicted worry and anger about crime. Believing the media are a reliable source of information about crime predicted more anger and more support for the justice system. Personal and network members' victimization was also linked to attitudes. Other network contacts, including knowing police or correctional officers or knowing someone who had been arrested or incarcerated, had limited effects. The results support the problem frame and cultivation theses in that media framing and media consumption influence attitudes about crime, as do certain real-world experiences.